PENGOLAHAN LIMBAH CAIR DI MASJID AGUNG SUMENEP DENGAN SISTEM ECODRAIN - Cholilul Chayati; Darma Jasuli (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
Drainage is very important because it is used to drain excess water from the ground. so that it cannot be separated from the development of an area. Drainage is needed to prevent excess water that can cause puddles in an area or place. The Great Mosque of Sumenep is one of the destinations for religious tourism which is a mandatory visit for tourists. And is the main mosque in Sumenep with 2463 congregations every day. At the Great Mosque. liquid waste is immediately disposed of into the existing drainage channel. no liquid waste treatment has been produced. The volume of liquid waste produced by the contact person from the bathroom and place of ablution is 24.630 liters / person or 24.63 m³ / day. Ecodrai with a sanitary pond with 4 stages of waste processing process using plants as waste decomposers.